The developmental origins of disease: implications for primary prevention of diseases in children (and the rest of us) - Cranor, Carl F. (European Journal of Oncology and Environmental Health, 2016)
Recent research into the developmental origins of disease, revealing risks to children, shows why the vast majority of laws in the U.S. and probably those of many other countries poorly protect children from toxic substances, and what we might learn from this for other circumstances. Once we recognize numerous limitations of current laws, it becomes incumbent upon decision makers to find and adopt strategies to better protect children. In the first instance, laws that permit exposures of chemical substances to children and adults without any knowledge of their toxicity should be modified a) to require toxicity testing of new products and b) to increase the toxicity testing of products (and pollutants) already in commerce. Because instituting the political change that would likely be necessary, in the short to intermediate term scientists should seek to use existing scientific tools to more quickly identify toxic products and to develop new types of studies with the goal of better preventing harm to the public. Scientific research may to some extent compensate for legal inaction.